1993
DOI: 10.1172/jci116417
|View full text |Cite
|
Sign up to set email alerts
|

CD10/neutral endopeptidase 24.11 regulates fetal lung growth and maturation in utero by potentiating endogenous bombesin-like peptides.

Abstract: Bombesin-like peptides (BLPs) are mitogens for bronchial epithelial cells and small cell lung carcinomas, and increase fetal lung growth and maturation in utero and in organ cultures. BLPs are hydrolyzed by the enzyme CD10/neutral endopeptidase 24.11 (CD10/NEP) which is expressed in bronchial epithelium and functions to inhibit BLP-mediated growth of small cell lung carcinomas. To determine whether CDI0/NEP regulates peptide-mediated lung development, we administered a specific CD1O/NEP inhibitor, SCH32615, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
36
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 33 publications
5
36
0
2
Order By: Relevance
“…Previously, we demonstrated that BLP promotes growth and maturation of fetal murine lung (8,37). In the present study of bombesin-treated outbred mice, we demonstrate a threefold increase in both cell proliferation and the prevalence of myofibroblasts in the distal lung parenchyma, consistent with early signs of pulmonary interstitial fibrosis, such as occurs with BPD.…”
Section: Discussionsupporting
confidence: 83%
“…Previously, we demonstrated that BLP promotes growth and maturation of fetal murine lung (8,37). In the present study of bombesin-treated outbred mice, we demonstrate a threefold increase in both cell proliferation and the prevalence of myofibroblasts in the distal lung parenchyma, consistent with early signs of pulmonary interstitial fibrosis, such as occurs with BPD.…”
Section: Discussionsupporting
confidence: 83%
“…In our previous work, we demonstrated that BLP is important for type II cell differentiation and surfactant synthesis as well as generalized cell proliferation in both murine and human fetal lung in organ culture and in murine lung in utero (40)(41)(42)(43). Subsequent work in other laboratories confirmed and extended this result to isolated rat primary type II cell cultures (44,45), in which BLP stimulated surfactant secretion as well as synthesis (44).…”
Section: Discussionmentioning
confidence: 72%
“…In the brain, it is responsible for the inactivation of the enkephalins (Malfroy et al, 1978), whereas in lung it down-regulates neurogenic inflammation by reducing local levels of tachykinins (Martins et al, 1990;Nadel, 1990;Nadel and Borson, 1991). It is also responsible for control of GRP-induced growth in fetal lung, where alterations in levels of GRP throughout maturation are accompanied by corresponding changes in EC 3.4.24.11 levels (King et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme inactivates by cleaving the His25-Leu26 bond; the His20-Trp21 bond is also cleaved, but to a much lesser extent (Bunnett et al, 1988). Other work suggests that high levels of neutral endopeptidase EC 24.11 regulate GRP-mediated growth of fetal lungs (King et al, 1993), and there is also considerable evidence that this enzyme regulates extracellular GRP levels in SCLC cell lines. Colony formation in SCLC cell lines that secrete GRP-like peptides is potentiated when neutral endopeptidase EC 24.11 is inhibited using phosphoramidon.…”
mentioning
confidence: 99%